Enhancement of refrigerant-side condensation heat transfer performance of additively-manufactured air cooled heat exchangers - Koh, Wei Wen (Nanyang Technological University, 2022)
This report presents both numerical and experimental data used as validation to prove the heat transfer enhancement of a novel air-cooled heat exchanger, if any. Steady-state, two-phase condensation is simulated using commercial software, ANSYS and its package Fluent, for two distinct mini channel geometries – Circular and Triangular – of 1-mm diameter, where the numerical model is first validated against results of an established numerical model that showcased an acceptable degree of accuracy. A low-Reynolds modified form of the SST k-ω turbulent model along with the VOF method, is employed to visualise and track the vapour-liquid flow interface throughout the computational domain where the effects of gravity, interfacial shear stress, and surface tension were factored in. Condensation in simulations is achieved by having a ΔT = 10 K between Tsat and Tw. Simulation results determine that the triangular cross-sectional channel exhibits better heat transfer performance compared to its circular counterpart, consistent with the results reported by other investigators. In the present work, R134a is used as the working refrigerant for both simulation and experimental runs. On the experimental front, the performance of a conventional heat exchanger is evaluated where R134a is condensed in a test section of a wind tunnel. Aggregating both numerical and experimental results, the data show that the conventional heat exchanger exhibits poorer heat transfer coefficients compared to that of simulation results. While operating conditions are not completely identical between simulations and experimental runs, there is sufficient evidence to hypothesize that the novel heat exchanger in a triangular multi-port configuration, will outperform the existing conventional heat exchanger in heat transfer capabilities.